2016
DOI: 10.5558/tfc2016-021
|View full text |Cite
|
Sign up to set email alerts
|

Germination and establishment of natural red spruce (Picea rubens) seedlings in silvicultural gaps of different sizes

Abstract: Red spruce (Picea rubens Sarg.) is difficult to regenerate from natural seeding following silvicultural treatment. In order to study its germination and establishment, we monitored the dynamics of new seedlings over 10 years in silvicultural gaps of different sizes (small: < 100 m 2 , medium: 100-300 m 2 , large: > 700 m 2 ). Seedling density was higher in small gaps but survival rate did not exceed 40%, leaving few live seedlings after 10 years (< 200 ha -1 ). Mounds were the best microtopography for seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Young spruce shoots are abundant in vitamin C, and they are a popular folk remedy for coughs, colds, respiratory ailments, and pain. Spruce oil has antibacterial and antifungal properties [16][17][18][19][20]. In survival situations, spruce needles can be directly consumed or boiled into tea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young spruce shoots are abundant in vitamin C, and they are a popular folk remedy for coughs, colds, respiratory ailments, and pain. Spruce oil has antibacterial and antifungal properties [16][17][18][19][20]. In survival situations, spruce needles can be directly consumed or boiled into tea.…”
Section: Introductionmentioning
confidence: 99%
“…Spruce needles, young twigs, and essential oils are used to brew spruce beer. Spruce seeds and young plants are readily consumed by various forest animals, which often cause substantial damage to spruce stands [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Lhotka et al (2018), examined the effects of gap size on species composition and volume increases over fifty years in oak stands and found that species diversity and growth were significantly reduced in light limited small gaps (200 m 2 ). The effects of gap size on regeneration species composition, survival, light availability, seedling density, and growth responses are well documented (Brokaw, 1985;Dumais and Prevost, 2016;Nakashizuka, 1984;Qinghong and Hytteborn, 1991;Rentch et al, 2016;Wu et al, 1999). Changes in irradiance have large impacts on seedling development and growth (Gilbert et al 2001;Denslow 1987).…”
Section: Light Regimesmentioning
confidence: 99%
“…This would suggest that competition may be greater in larger gaps or gap centers, where canopy openings permit more direct light to hit the forest floor (Brokaw and Busing, 2000;Diaci et al, 2012;Dumais and Prevost, 2016;Vilhar et al, 2014). In some studies however, established shade-tolerant seedlings can respond to the light regime change and grow into the canopy (Wu et al 1999;Yamamoto 2000;Couwenberghe et al 2010;Copenheaver et al 2014).…”
Section: Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation